ANTICORPOS ANTIMIOCARDIO NA DOENCA DE CHAGAS CRONICA. CORRELACAO ENTRE A SOROLOGIA E A ELETROCARDIOGRAFIA - Trezza, E.; Tucci, P. J.F.; Buffollo, E.; Montenegro, M. R.G. (My University, 1975)
The purpose of this study was to detect antimyocardial antibodies in the sera of patients with chronic Chagas' disease and correlate serological with EKG findings. The diagnosis of Chagas' disease was made based on epidemiological, clinical and serological data (complement fixation test and indirect immunofluorescence reaction with T. cruzi). Antimyocardial antibodies were detected by the indirect immunofluorescence method, with cryostat sections of rat heart as antigen. The serum was absorbed with rat liver extract to eliminate nonspecific reactions. The study included 131 chagasic patients, 31 normal persons (negative controls) and 32 patients submitted to cardiac surgery for correction of rheumatic valvular disease (positive controls), whose sera were obtained 8 to 21 days after surgery. Serum samples were randomly numbered prior to the immunological studies. Antimyocardial antibodies were found in 6.4% of the normal controls, 56.2% of the patients with rheumatic heart disease and 32.8% of the chagasic patients. The differences among the three groups were statistically significant (p < 0.05). There were no differences as to sex. Serum levels were seldom greater than 1:8. Organ specificity of the antibodies was confirmed by negativation of the reactions when positive sera were absorbed with rat heart extract. Gamma globulin bound to endocardium, pericardium and the intima and adventitia of vessels was observed with positive sera as well as with almost all sera from chagasic patients who exhibited negative reactions with cardiac muscle. No explanation was found for this fact. Comparison of the immunologic and EKG findings disclosed a positive correlation between antimyocardial antibodies and left atrial hypertrophy (p < 0.05). Ventricular ectopic beats, abnormal ventricular repolarization, electrical signs of inactive areas and right bundle branch block were more frequent in the positive than in the negative group; these differences were not statistically significant. Normal EKG prevailed in the chagasic patients without antimyocardial antibodies.
Antibodies to heart tissue in chronic Chagas' disease. Correlation between serological results and the electrocardiogram